Systematic expression analysis of genes related to generation of action potentials in human iPS cell-derived cardiomyocytes - Masami Kodama; Kazuharu Furutani; Reiko Kimura; Tomoko Ando; Kazuho Sakamoto; Shushi Nagamori; Takashi Ashihara; Yoshihisa Kurachi; Yuko Sekino; Tetsushi Furukawa; Yasunari Kanda; Junko Kurokawa (Elsevier, 2019)
Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are a valuable tool to characterize the pharmacology and toxic effects of drugs on heart cells. In particular, hiPSC-CMs can be used to identify drugs that generate arrhythmias. However, it is unclear whether the expression of genes related to generation of CM action potentials differs between hiPSC-CM cell lines and the mature human heart. To address this, we obtained accurate gene expression profiles of commercially available hiPSC-CM cell lines with quantitative real time RT-PCR analysis. Expression analysis of ten cardiac proteins important for generation of action potentials and three cardiac proteins important for muscle contractility was performed using GAPDH for normalization. Comparison revealed large variations in expression levels among hiPSC-CM cell lines and between hiPSC-CMs and normal human heart. In general, gene expression in hiPSC-CM cell lines was more similar to an immature, stem-like cell than a mature cardiomyocyte from human heart samples. These results provide quantitative information about differences in gene expression between hiPSC-CM cell lines, essential for interpreting pharmacology experiments. Our approach can be used as an experimental guideline for future research on gene expression in hiPSC-CMs. Keywords: iPS cells, Quantitative real time-PCR, Reference gene, Cardiac ion channels, Action potential